Polymerase chain reaction in meat species identification - Zurak, Dora; Kljak, Kristina; Cvrtila, Željka (2021)
Food is considered authentic or genuine if the product or its contents conform to the original condition and label claims. Deviations from assertions and information on the declaration are considered non-compliances with food regulations. Due to the increased awareness of the problem and negative impact of food fraud, meat consumption is significantly influenced by consumer perceptions of food quality and safety. Therefore, accurate labelling is one of the most important factors influencing consumer preferences in the selection and purchase of meat and meat products. For this reason, analytical methods to verify the authenticity of meat and meat products are important to ensure product quality, food safety and consumer protection. The substitution of meat variety is not the only criterion for determining the authenticity of meat and meat products, but also the origin of the meat, the treatment of the meat and the addition of non-meat ingredients. Polymerase chain reaction (PCR) and its derived technologies have been shown to be the most suitable methods for species identification in raw and technologically processed meat. PCR methods are mainly based on the identification of the target region of mitochondrial DNA, which allows the detection of species in a wide range of meat products, including all domestic animals as well as game meat intended for human consumption. However, they also have some drawbacks. For example, random amplified polymorphic DNA (PCR-RAPD) is not suitable for species identification in meat mixtures as well as in thermally processed meat. On the other hand, some methods are expensive, time consuming and there are difficulties in interpreting the results. In this article, the main PCR-based methods for meat species identification are presented and described.
Hrana se smatra autentičnom kada proizvod ili njegov sadržaj odgovaraju izvornom stanju i podacima na deklaraciji. Odstupanja od tvrdnji i navoda na deklaraciji smatraju se nesukladnostima s propisima o hrani. Zbog pojačane svijesti o problemu i negativnim učincima patvorenja hrane, na konzumaciju mesa značajno utječe percepcija potrošača o kvaliteti i sigurnosti hrane, pri čemu je ispravno deklariranje jedan od najvažnijih čimbenika koji utječe na preferencije u vidu odabira i kupovine mesa i mesnih proizvoda. Zbog navedenog razloga, analitičke metode koje se upotrebljavaju za provjeru autentičnosti važne su radi osiguranja kvalitete proizvoda, sigurnosti hrane, ali i zaštite potrošača. Zamjena vrsta mesa nije jedini kriterij kojim se utvrđuje njegova autentičnost, te obuhvaća i podrijetlo mesa, način njegove prerade, kao i dodatak ostalih sastojaka. Lančana reakcija polimerazom (PCR) i njezine modifikacije prepoznate su kao najprikladnije metode za identifikaciju vrsta u sirovom i tehnološki prerađenom mesu. PCR metode uglavnom se temelje na identifikaciji ciljane regije mitohondrijske DNK, što omogućuje detekciju vrsta u širokom spektru mesnih proizvoda, uključujući sve domaće životinje, kao i meso divljači koje se upotrebljava u prehrani ljudi. Unatoč navedenome, PCR metode posjeduju određene nedostatke, te tako primjerice, PCR-RAPD nije prikladan za identifikaciju vrsta mesa u mješavinama, kao i termički prerađenog mesa, dok su neke metode skupe, dugotrajne i posjeduju poteškoće vezane uz interpretaciju rezultata. U ovom radu predstavljene su i opisane najvažnije metode koje se temelje na PCR tehnici, a upotrebljavaju se za identifikaciju vrsta mesa.
Lebensmittel gelten als authentisch, wenn das Produkt oder sein Inhalt mit dem Originalzustand und den Angaben auf der Deklaration übereinstimmt. Abweichungen von den Behauptungen und Angaben auf der Deklaration werden als Verstöße gegen die Lebensmittelvorschriften angesehen. Aufgrund des gestiegenen Bewusstseins für das Problem und die negativen Auswirkungen von Lebensmittelbetrug wird der Fleischkonsum maßgeblich von der Wahrnehmung der Verbraucher in Bezug auf die Lebensmittelqualität und Sicherheit beeinflusst. Daher ist eine genaue Etikettierung einer der wichtigsten Faktoren, die die Verbraucherpräferenzen bei der Auswahl und dem Kauf von Fleisch und Fleischerzeugnissen beeinflussen. Aus diesem Grund sind Analysemethoden zur Überprüfung der Echtheit von Fleisch und Fleischerzeugnissen wichtig, um die Produktqualität, Lebensmittelsicherheit und den Verbraucherschutz zu gewährleisten. Die Substitution von Fleischsorten ist nicht das einzige Kriterium für die Bestimmung der Echtheit von Fleisch und Fleischerzeugnissen, sondern auch die Herkunft des Fleisches, die Behandlung des Fleisches und der Zusatz von sonstigen Zutaten. Die Polymerase-Kettenreaktion (PCR) und die davon abgeleiteten Technologien haben sich als die am besten geeigneten Methoden zur Identifizierung von Arten in rohem und technologisch verarbeitetem Fleisch erwiesen. Die PCR-Methoden basieren hauptsächlich auf der Identifizierung der Zielregion der mitochondrialen DNA, was den Nachweis von Arten in einer breiten Palette von Fleischerzeugnissen ermöglicht, einschließlich aller Haustiere und des für den menschlichen Verzehr bestimmten Wildfleischs. Sie haben jedoch auch einige Nachteile. So eignet sich beispielsweise die zufällig amplifizierte polymorphe DNA (PCR-RAPD) nicht für den Artennachweis in Fleischmischungen und in thermisch verarbeitetem Fleisch. Andererseits sind einige Methoden teuer und zeitaufwendig, und die Ergebnisse sind schwer zu interpretieren.
Los alimentos se consideran auténticos cuando el producto o su contenido corresponde al estado original y a los datos de la declaración. Las divergencias de las declaraciones se consideran incumplimientos de las regulaciones alimentarias. Debido a la mayor conciencia sobre el problema y los efectos negativos de la falsificación de los alimentos, el consumo de carne está significativamente influenciado por las percepciones de los consumidores sobre la calidad y seguridad de los alimentos, siendo la declaración correcta uno de los factores más importantes que influyen sobre las preferencia a la hora de elegir y comprar la carne y los productos cárnicos. Por esta razón, los métodos analíticos utilizados para verificar la autenticidad son importantes para garantizar la calidad del producto, la seguridad alimentaria, pero también la protección del consumidor. La sustitución de tipos de carne no es el único criterio para determinar su autenticidad e incluye el origen de la carne, el método de procesamiento, así como la adición de otros ingredientes. La reacción en cadena de la polimerasa (PCR) y sus modificaciones son identificadas como los métodos más apropiados para identificar los tipos de carne en la carne cruda y la carne procesada tecnológicamente. Los métodos de PCR están basados principalmente en la identificación de las secuencias cortas de la ADN mitocondrial, lo que permite la detección de especies en una amplia gama de productos cárnicos, incluidos todos los animales domésticos, así como la carne de caza para el consumo humano. A pesar de esto, los métodos de PCR tienen ciertas deficiencias, por lo que, por ejemplo, el PCR - RAPD no es adecuado para identificar tipos de carne en mezclas, así como carne procesada térmicamente, mientras que algunos métodos son costosos, consumen mucho tiempo y dan resultados difíciles para interpretar.
Il cibo è considerato autentico o genuino quando il prodotto o il suo contenuto corrispondono alla condizione originale e ai dati dell’etichetta. Ogni deviazione dalle asserzioni e dalle indicazioni contenute nell’etichetta è considerata difformità rispetto alla normativa sul cibo. A causa della maggior consapevolezza rispetto al problema e riguardo agli effetti negativi del cibo contraffatto, sulla consumazione della carne incide significativamente la percezione del consumatore circa la qualità e la sicurezza del cibo, laddove la corretta etichettatura è uno dei fattori più importanti che incidono tanto sulle preferenze riguardo alla scelta, quanto sull’acquisto della carne e dei prodotti a base di carne. Per quanto detto, i metodi analitici che si utilizzano per verificare l’autenticità sono importanti ai fini di garantire non solo la qualità del prodotto e la sicurezza alimentare, ma anche la tutela dei consumatori. La sostituzione della varietà di carne non è l’unico criterio per accertarne l’autenticità, e comprende anche l’origine della carne, le modalità della sua lavorazione e, infine, l’aggiunta di altri ingredienti. La reazione a catena della polimerasi (PCR) e le sue modificazioni sono riconosciute come il metodo più idoneo all’identificazione delle varietà nella carne cruda e in quella sottoposta a processo tecnologico di lavorazione. I metodi PCR si basano, in linea di massima, sull’identificazione di una regione del DNA mitocondriale, il che consente la individuazione della varietà in una vasta gamma di prodotti a base di carne, compresi tutti gli animali d’allevamento e la carne degli animali selvatici che viene utilizzata nell’alimentazione umana.
Bibliografija: 56 jed.
Abstract ; Sažetak ; Zusammenfassung ; Resumen ; Riassunto.
Keywords: Polimerazna lančana reakcija -- Meso -- Patvorenje mesa -- Autentičnost